Youthsâ€™ Language and Resistance Identity - Umukoro, Beauty Esiophunevu; Ovweriavwose, Florence Eniyome (NIU Journal of Social Sciences, 2017)
The emergence of globalization in the 21st Century has attendant challenges on language especially among youths. Youths have employed language in a most remarkable way to forge new identity for themselves. The most influential social group being youths have peculiar language which is in sharp contrast to the language of any other social group. In the content of this study, the term youth has special application to adolescents, which is not just a biological age but a social institution which has established itself in this modern era. They have made huge linguistic innovations hence they are viewed as linguistic â€œmoversâ€ and â€œshakersâ€™ (Kerswill, 1996). This paper attempts to examine different patterns of youth language, their vocabularies, structure and underlying meaning. The paper also makes effort to investigate ways in which youth language patterns or types are at variance with that of adults. The various expressions that are analyzed in this paper are representative of youth language and the researchers arrived at these by carefully paying attention to the discussions of some youths (students) in the College of Education, Warri. Keywords : language, globalization, identity, youth, adolescents, innovations and linguistics.